PERCEPTION OF HEIGHT AND CATEGORIZATION OF BRAZILIAN PORTUGUESE FRONT VOWELS - Silva, Daniel Márcio Rodrigues; Rothe-Neves, Rui (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
Cross-linguistic typological observations and theoretical models in phonology suggest that certain speech sound distinctions are more complex then others. An example is the case of the opposition between mid-high and mid-low vowels, usually thought to be more complex than the opposition between high and mid vowels. The present study provides experimental evidence on speech sound perception that supports that notion. Native Brazilian Portuguese speakers performed vowel classification tasks involving either the distinction between the front high mid /e/ and the front high /i/, or the distinction between the front high mid /e/ and the front low mid /ɛ/ vowel. Measures of response time and discriminability (d’) at the vowel category boundaries were obtained. Participants showed significantly slower responses and lower d’ values in the “e-ɛ” as compared to the “i-e” classification task. Results indicate that perceptually distinguishing /e/ from /ɛ/ requires more processing time and resources, and involves more complex information than distinguishing /e/ from /i/.